(3TQM GdCSHGH hGdYdGeGJ ddSeQbfOis - (3HQgGf GdOjf fajS Hf YhV Hf Mcje GdcQeGfis; (3GdfLjH GdSeQbfOj , eMeO Hf Ydj Hf YeQ GdSeQbfOj, fLjH GdOjf CHh MGeO,J (B619 (3g` s
(3ChdgG (B:s
(3aEf GdYHO GdabjQEdi Gddg hcGf bSe GdCeQGV GdLRFjI ef gPG Gdaf de jbUO CMO GdCaGVd Edi GdBf dJaSjQg hJTQjMg aCQOJ Cf CcTa Yf hLhg ahGFO gPG Gdaf bGd GdeUfa GdUOGY Cde s
(3BNQgG (B:s
(3hCf jbJUQ Ydi eKd LhR GdSQhQ hGdCHgd , hSGFQ eG jfaY ai VeGO GdaJb , aEfgG JTO GdYVh hJfTa GdQWhHGJ hGddg CYde s
(3fSNI KGfjIs
(3hHChdgG agQS JaUjdi ddehVhYGJs
(3jbY ai YTQ hQbGJs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdWHs